KNOWLEDGE MANAGEMENT STRATEGY TO IMPROVE BUSINESS SECTOR - Mohajan, Haradhan Kumar (Annals of Spiru Haret University. Economic Series, 2017)
Every organization needs the proper knowledge management (KM) strategy for the development of the organization. In the last decades the business environment has changed and recently it becomes more dynamic and more complex. At present KM is valuable not only for individuals, and organizations, but also, for global humanity. So, the directors of the organizations must emphasize on the existing knowledge and try to develop them to achieve the competitive advantage. The purpose of the study is to explore the recent KM practice in the organizations and to show the ways to develop the new KM strategy in future. An attempt has been taken here to apply KM strategy in business performance, business intelligence, and e-business.